Consumo de bebidas alcoólicas por jovens: implicações para o marketing social. - Bastos, Adriana de Fatima Valente (2013)
The central theme of thesis lies upon alcohol consumption amongst young people, under a social marketing perspective. The research is justified by an analysis on the consumer as an agent who generates imbalance in the exchange system, deriving from excessive alcohol consumption in youth. This indication has as immediate consequence a broadening of the marketing view either as an activity or a knowledge, thus becoming an area oriented for the system s balance. This study aimed to analyze determining factors for alcohol consumption predisposition, to measure and to hypothesize, based on the theoretical model proposed. Hence, a literature review on prospective constructs which might influence alcohol consumption oh youngsters was carried. To enable the empirical research s operationalization, 322 questionnaires were administered, with young people from 18 to 30 years old. With presential application in the city João Pessoa. Generally speaking, result show that social reference (family and friends), sociability and personal satisfaction influence on the perceived risk, social stigmatization and feeling of self-confidence was found in the study s analysis context. In the study s final part, theoretical and practical implications are presented along with limitations and recommendations for future research.